(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The construction projects in general and the school buildings in particular in Iraq are suffering from an increasing number of risks, especially the financial risks facing the construction projects, because there are insufficient sources of funding to supplement the work and the delay of most school buildings projects, despite the need to do so. On the basic objectives of the construction project in order to improve the implementation of the school building projects, so it is necessary to use some hypotheses, which is the choice of the best solutions, treatments and proposals, which attendance in the study of the latest possible In order to achieve the advancement of school buildings projects and efficiency and improve performance, a set of proposed solutions are then presented. These solutions are examined and the future results of each solution are identified and useful in addressing the specific problem and the future impact of its application. The methodology used to search for indicators from the framework Theoretical and practical solutions to come out with a number of conclusions and recommendations aimed at achieving the objectives of the research